Polyurethane grouting material and preparation method thereof
By introducing modifiers and precise control of process steps in the polyurethane grouting material, the problems of high curing shrinkage, poor bonding performance, insufficient durability and poor construction performance of the polyurethane grouting material are solved, and a higher performance grouting material is achieved .
Patent Information
- Application Number
- CN202411609562.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
The existing polyurethane grouting materials may cause large shrinkage during the curing process, resulting in a decrease in the bonding performance between the material and the base surface, and insufficient durability under harsh environments or long-term load conditions, and construction performance also needs to be optimized.
A polyurethane grout with excellent comprehensive performance is prepared by introducing specific modifiers such as bentonite, nano-silica powder and fluorocarbon emulsions, and using precisely controlled dehydration, mixing, degassing and reaction processes.
It achieves lower curing shrinkage, stronger bonding performance, better durability and better construction adaptability, meeting the strict requirements of the construction industry for high-performance grouting materials.
Smart Images

Figure BDA0005130593790000131 
Figure BDA0005130593790000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building waterproof materials, and in particular to a polyurethane grouting material and a preparation method thereof. Background Art
[0002] Polyurethane grouting materials have been widely used in the reinforcement, waterproofing and sealing of building structures due to their excellent bonding properties, good elasticity and outstanding chemical corrosion resistance. Traditional polyurethane grouting materials are mainly produced by the reaction of polyether polyols and isocyanates. By adjusting the ratio of the two and adding different types of additives, grouting materials with different properties can be obtained. However, as the construction industry's requirements for material performance increase, the performance of existing polyurethane grouting materials is still limited in certain application scenarios.
[0003] First, traditional grouting materials may shrink significantly during the curing process, resulting in a decrease in the bonding performance between the material and the substrate, or even cracks, which will affect the long-term waterproofing effect. Secondly, some grouting materials are not durable enough to meet the requirements of use in harsh environments or long-term load conditions. In addition, the construction performance of traditional grouting materials needs to be optimized. For example, it is difficult to construct in high humidity or underwater environments.
[0004] China's invention patent CN112876635B discloses a low-foaming, strong-bonding elastic polyurethane grouting material and its preparation method. The raw materials of the grouting material are composed of the following raw materials in limited weight proportions: polyether polyol, polyether diol, isocyanate, viscosity-increasing resin, liquid filler and solvent. The preparation method is to react polyether polyol with excess isocyanate to prepare a polyurethane grouting material prepolymer with isocyanate end-capping and sufficient free amount; then use polyether diol, viscosity-increasing resin, liquid filler and remaining excess isocyanate to react to prepare polyurethane adhesive prepolymer; mix the prepolymer, add solvent to obtain the product. The grouting material obtained by the invention can be injected into the concrete cracks by a grouting machine to form a closed-cell foamed elastic consolidation body that can be bonded to the wet surface, so as to achieve full bonding with the side wall of the crack, thereby resisting the changes in the cracks caused by factors such as building deformation, and achieving the purpose of dynamic waterproofing, which is of great significance for solving building waterproofing projects. However, the polyurethane grouting material prepared by the invention has high volume shrinkage and dry-wet cycle expansion, and has a narrow scope of application. Summary of the invention
[0005] In view of the defects of the prior art, the present invention aims to provide a polyurethane grouting material with excellent comprehensive performance. Through the introduction of special functional agents, this material achieves lower curing shrinkage, stronger bonding performance, better durability and better construction adaptability, so as to meet the construction industry's stringent requirements for high-performance grouting materials.
[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0007] A polyurethane grouting material, composed of the following components in parts by weight:
[0008] 15-25 parts of polyether polyol 400, 12-19 parts of functional agent, 8-10 parts of hexamethylene diisocyanate, 13-18 parts of polyether diol 210, 10-15 parts of dimethylsiloxane, 10-15 parts of polymethylene polyphenyl polyisocyanate, 13-18 parts of diisononyl phthalate, and 3-5 parts of xylene.
[0009] The preparation method of the polyurethane grouting material is as follows:
[0010] Step 1, polyether polyol 400 and diisononyl phthalate are mixed with a functional agent, added into a reaction vessel equipped with vacuum reduced pressure distillation and stirring functions, the mixture is heated to 100-110° C., and dehydrated. After dehydration, the reaction temperature is lowered to 60-80° C., hexamethylene diisocyanate is added under normal pressure, the reaction temperature is maintained at 70-80° C., and the reaction is continued for 2-5 hours to form a pretreated product;
[0011] Step 2, polyether diol 210, functional agent and dimethylsiloxane are mixed, and heated to 100-120° C. in a reaction vessel with vacuum distillation and stirring; dehydration treatment; after dehydration, the temperature is lowered to 60-80° C., and polymethylene polyphenyl polyisocyanate is added under normal pressure; the temperature is controlled at 70-80° C., and the treatment is continued for 2-5 hours to prepare a reinforcing agent;
[0012] Step 3: Cool the pretreated material obtained in step 1 to 50-70° C. At this temperature, add the reinforcing agent obtained in step 2 to the pretreated material, degas the material to ensure that the mixture is uniform and remove bubbles, and finally, add xylene and stir for 5-15 minutes to obtain a polyurethane grouting material.
[0013] The functional agent is a mixture of a thixotropic agent, a modifier and a terpene resin in a weight ratio of 2-4:3-5:2-4.
[0014] The thixotropic agent is one or more of polyamide wax, polyethylene wax, castor oil, bentonite, fumed silica, kaolin, calcium carbonate and attapulgite.
[0015] The dehydration treatment in step 1 and step 2 is independently performed under a vacuum environment of 0.08 to 0.09 MPa for 0.5 to 2 hours.
[0016] The degassing treatment in step 3 is to stir in a vacuum environment of 0.08 to 0.09 MPa and perform vacuum degassing treatment for 10 to 30 minutes.
[0017] The preparation method of the modifier is as follows, in parts by weight:
[0018] S1. Weigh 3-5 parts of bentonite, 1-2 parts of nano-silicon powder, 0.4-0.8 parts of sodium aluminate and 0.5-1 parts of kaolin as starting materials; mix these materials in a blender at a speed of 1500-2500 rpm for 10-30 minutes to ensure that the components are evenly dispersed to form a consistent mixed powder;
[0019] S2, transferring the mixed powder obtained in step S1 to a reaction kettle, adding 0.4 to 0.6 parts of a surfactant during this process, and heating the system to 150 to 170° C., maintaining this temperature for 20 to 40 minutes for an adsorption modification process to form a modified powder;
[0020] S3. Use a sprayer to evenly spray 0.4 to 0.6 parts of fluorocarbon emulsion on the surface of the modified powder prepared in step S2 for 3 to 10 minutes, while maintaining the temperature in the reactor at 160°C; after the spraying is completed, reduce the temperature in the reactor to 130 to 150°C and maintain it at this temperature for 0.5 to 2 hours to promote complete evaporation of water in the material and ensure dehydration and drying of the powder to obtain a modifier.
[0021] The surfactant is composed of sodium palmitate and glycerol monostearate in a mass ratio of 2-4:1-3.
[0022] In the preparation method of the polyurethane grouting material of the present invention, each substance has the following functions:
[0023] As one of the main raw materials of polyurethane grouting materials, polyether polyol 400 provides the required hydroxyl groups and participates in the chemical reaction with isocyanate to form the main structure of polyurethane.
[0024] The functional agent is a mixture of polyamide wax, modifier and terpene resin, and is used to improve the physical properties of the grouting material, such as enhancing adhesion, increasing flexibility and improving construction performance.
[0025] As one of the main raw materials of polyurethane grouting materials, hexamethylene diisocyanate provides isocyanate groups and reacts with polyether polyols to form polyurethane.
[0026] Polyether diol 210 provides additional hydroxyl groups to participate in the reaction with isocyanate, which can adjust the properties of polyurethane grouting materials, such as flexibility and reactivity.
[0027] Dimethylsiloxane may be used to adjust the viscosity and fluidity of the grouting material and improve its construction performance during application.
[0028] Polymethylene polyphenyl polyisocyanate, as another isocyanate, reacts with polyether diol and functional agent to enhance the crosslinking density and mechanical strength of the grouting material.
[0029] Fluorocarbon emulsions are used in modifiers to provide hydrophobic properties and enhance the weather resistance and surface properties of the grout.
[0030] Bentonite, nano-silica powder, sodium aluminate and kaolin are used as the starting materials of the modifier. After mixing, these materials are treated with surfactants and fluorocarbon emulsions to form powders with good dispersibility and modification effects.
[0031] Sodium palmitate and glycerol monostearate are used as surfactants in the preparation process of the modifier to help the formation of modified powder and improve its dispersibility in the grouting material.
[0032] Xylene, as a solvent, may be used to adjust the viscosity and fluidity of the final grout.
[0033] Through the synergistic effect of these substances, the polyurethane grouting material of the present invention is intended to achieve excellent physical properties and construction performance to meet specific application requirements.
[0034] Compared with the prior art, it has the following beneficial effects:
[0035] 1) By introducing specific modifiers, including inorganic materials such as bentonite and nano-silicon powder and organic materials such as fluorocarbon emulsion, the polyurethane grouting material of the present invention is significantly improved in physical and chemical properties, including enhanced bonding strength and durability, and improved hydrophobicity and stability.
[0036] 2) The present invention adopts precisely controlled dehydration, mixing, degassing and reaction process steps to ensure the uniformity and consistency of the grouting material, reduce bubbles and non-uniformity, thereby improving the construction performance of the material and the reliability of the final application.
[0037] 3) The polyurethane grouting material of the present invention exhibits a lower volume shrinkage and dry-wet cycle expansion, which means that the material is more stable in long-term applications and can adapt to environmental changes without performance degradation, especially in applications such as building waterproofing and structural reinforcement, and can effectively prevent leakage and improve the long-term stability of the structure. DETAILED DESCRIPTION
[0038] Main sources of substances:
[0039] Polyether polyol 400, model: PPG-400, comes from Shanghai Beko Chemical Co., Ltd.
[0040] Polyether diol 210, model: PPG-1000, comes from Shanghai Beko Chemical Co., Ltd.
[0041] Polymethylene polyphenyl polyisocyanate, CAS: 9016-87-9.
[0042] Bentonite: 800 mesh, calcium bentonite.
[0043] The nano silicon powder is 35nm and comes from Beijing Dekedaojin Technology Co., Ltd.
[0044] The kaolin is calcined kaolin, 1250 mesh.
[0045] Fluorocarbon emulsion, sourced from Zhengzhou Jinbang Chemical Co., Ltd., viscosity (25°C): 19000 Pa·s.
[0046] The polyamide waxes are all from Taiyuan Metxon Technology Co., Ltd., model MT6650.
[0047] The terpene resin is from Kraton Chemical (USA), model TRA25L.
[0048] Polydimethylsiloxane emulsion, from German Digo Glide100, is a white emulsion; the solvent is a mixture of water and ethanol with a volume ratio of 3:1.
[0049] Polymethylphenylsiloxane was obtained from IOTA-704 of Iota Silicone Oil Co., Ltd.
[0050] Polymethylhydrogensiloxane is from Aldrich catalog number 176206, Mn=1700-3200 g / mol, CAS number 63148-57-2.
[0051] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.
[0052] The design idea of the present invention is to develop a high-performance polyurethane grouting material that combines a variety of modified materials and precise process control. By combining basic components such as polyether polyols, functional agents and isocyanates with specific modifiers, which are mixed with raw materials such as bentonite, nano-silicon powder, sodium aluminate and kaolin, and treated with surfactants and fluorocarbon emulsions to enhance their performance, a systematic modification of the grouting material is achieved. This modification not only improves the hydrophobicity, stability and mechanical properties of the material, but also ensures the uniformity and practicality of the final product through precisely controlled dehydration, mixing and degassing steps. The preparation method of the present invention pays attention to details and systematic optimization, aiming to provide a high-performance polyurethane grouting material with wide application potential in the fields of building waterproofing and structural reinforcement.
[0053] Example 1
[0054] A preparation method of polyurethane grouting material is as follows:
[0055] Step 1, 20kg of polyether polyol 400 and 15kg of diisononyl phthalate are mixed with 12kg of a functional agent, and added into a reaction vessel equipped with vacuum decompression distillation and stirring functions, the mixture is heated to 110°C, and dehydrated for 1 hour under a vacuum environment of 0.085MPa. After dehydration, the reaction temperature is lowered to 70°C, 9kg of hexamethylene diisocyanate is added under normal pressure, the reaction temperature is maintained at 75°C, and the reaction is continued for 4 hours to form a pretreated product;
[0056] Step 2, 15 kg of polyether diol 210, 3 kg of functional agent and 12 kg of dimethylsiloxane are mixed, and the mixture is heated to 110° C. in a reaction vessel with vacuum distillation and stirring; a dehydration treatment is performed for 1 hour under a vacuum condition of 0.085 MPa; after the dehydration is completed, the mixture is cooled to 70° C., and 12 kg of polymethylene polyphenyl polyisocyanate is added under normal pressure; the temperature is controlled at 75° C., and the treatment is continued for 4 hours to prepare a reinforcing agent;
[0057] Step 3: Cool the pretreated material obtained in step 1 to 60°C. At this temperature, add the reinforcing agent obtained in step 2 to the pretreated material, stir it in a vacuum environment of 0.085MPa and perform vacuum degassing for 20 minutes to ensure that the mixture is uniform and remove bubbles. Finally, add 4kg of xylene and stir it for 10 minutes to obtain a polyurethane grouting material.
[0058] The functional agent is a mixture of polyamide wax, a modifier and a terpene resin in a weight ratio of 3:4:3.
[0059] The preparation method of the modifier is as follows:
[0060] S1, weighing 4kg bentonite, 1.6kg nano-silicon powder, 0.6kg sodium aluminate and 0.8kg kaolin as starting materials; mixing these materials in a blender at a rate of 2000 rpm for 20 minutes to ensure that the components are evenly dispersed to form a consistent mixed powder;
[0061] S2. The mixed powder obtained in step S1 is transferred to a reactor. During this process, 0.5 kg of a surfactant is added, wherein the surfactant is sodium palmitate and glycerol monostearate in a mass ratio of 3:2, and the system is heated to 160° C. and maintained at this temperature for 30 minutes for an adsorption modification process to form a modified powder;
[0062] S3. Use a sprayer to evenly spray 0.5 kg of fluorocarbon emulsion on the surface of the modified powder prepared in step S2 for 6 minutes, while maintaining the temperature in the reactor at 160° C.; after the spraying is completed, the temperature in the reactor is lowered to 140° C. and maintained at this temperature for 1 hour to promote complete evaporation of water in the material and ensure dehydration and drying of the powder to obtain a modifier.
[0063] Example 2
[0064] The preparation method of a polyurethane grouting material is basically the same as that of Example 1, the only difference being that the preparation method of the modifier is different.
[0065] The preparation method of the modifier is as follows:
[0066] S1, weighing 4kg bentonite, 1.6kg nano-silicon powder, 0.6kg sodium aluminate and 0.8kg kaolin as starting materials; mixing these materials in a blender at a rate of 2000 rpm for 20 minutes to ensure that the components are evenly dispersed to form a consistent mixed powder;
[0067] S2. The mixed powder obtained in step S1 is transferred to a reactor. During this process, 0.5 kg of a surfactant is added, wherein the surfactant is sodium lauryl sulfate and glycerol monostearate in a mass ratio of 3:2, and the system is heated to 160° C. and maintained at this temperature for 30 minutes for an adsorption modification process to form a modified powder;
[0068] S3. Use a sprayer to evenly spray 0.5 kg of fluorocarbon emulsion on the surface of the modified powder prepared in step S2 for 6 minutes, while maintaining the temperature in the reactor at 160° C.; after the spraying is completed, the temperature in the reactor is lowered to 140° C. and maintained at this temperature for 1 hour to promote complete evaporation of water in the material and ensure dehydration and drying of the powder to obtain a modifier.
[0069] Example 3
[0070] The preparation method of a polyurethane grouting material is basically the same as that of Example 1, the only difference being that the preparation method of the modifier is different.
[0071] The preparation method of the modifier is as follows:
[0072] S1, weighing 4kg bentonite, 1.6kg nano-silicon powder, 0.6kg sodium aluminate and 0.8kg kaolin as starting materials; mixing these materials in a blender at a rate of 2000 rpm for 20 minutes to ensure that the components are evenly dispersed to form a consistent mixed powder;
[0073] S2. The mixed powder obtained in step S1 is transferred to a reactor. During this process, 0.5 kg of a surfactant is added, wherein the surfactant is sodium laurate and glycerol monostearate in a mass ratio of 3:2, and the system is heated to 160° C. and maintained at this temperature for 30 minutes for an adsorption modification process to form a modified powder;
[0074] S3. Use a sprayer to evenly spray 0.5 kg of fluorocarbon emulsion on the surface of the modified powder prepared in step S2 for 6 minutes, while maintaining the temperature in the reactor at 160° C.; after the spraying is completed, the temperature in the reactor is lowered to 140° C. and maintained at this temperature for 1 hour to promote complete evaporation of water in the material and ensure dehydration and drying of the powder to obtain a modifier.
[0075] Example 4
[0076] The preparation method of a polyurethane grouting material is basically the same as that of Example 1, the only difference being that the preparation method of the modifier is different.
[0077] The preparation method of the modifier is as follows:
[0078] S1, weighing 4kg bentonite, 1.6kg nano-silicon powder, 0.6kg sodium aluminate and 0.8kg kaolin as starting materials; mixing these materials in a blender at a rate of 2000 rpm for 20 minutes to ensure that the components are evenly dispersed to form a consistent mixed powder;
[0079] S2. The mixed powder obtained in step S1 is transferred to a reactor. During this process, 0.5 kg of a surfactant is added, wherein the surfactant is sodium stearate and glycerol monostearate in a mass ratio of 3:2, and the system is heated to 160° C. and maintained at this temperature for 30 minutes for an adsorption modification process to form a modified powder;
[0080] S3. Use a sprayer to evenly spray 0.5 kg of fluorocarbon emulsion on the surface of the modified powder prepared in step S2 for 6 minutes, while maintaining the temperature in the reactor at 160° C.; after the spraying is completed, the temperature in the reactor is lowered to 140° C. and maintained at this temperature for 1 hour to promote complete evaporation of water in the material and ensure dehydration and drying of the powder to obtain a modifier.
[0081] Example 5
[0082] The preparation method of a polyurethane grouting material is basically the same as that of Example 1, the only difference being that the preparation method of the modifier is different.
[0083] The preparation method of the modifier is as follows:
[0084] S1, weighing 4kg bentonite, 1.6kg nano-silicon powder, 0.6kg sodium aluminate and 0.8kg kaolin as starting materials; mixing these materials in a blender at a rate of 2000 rpm for 20 minutes to ensure that the components are evenly dispersed to form a consistent mixed powder;
[0085] S2. The mixed powder obtained in step S1 is transferred to a reactor. During this process, 0.5 kg of a surfactant is added, wherein the surfactant is sodium palmitate and glycerol monostearate in a mass ratio of 3:2, and the system is heated to 160° C. and maintained at this temperature for 30 minutes for an adsorption modification process to form a modified powder;
[0086] S3. Use a sprayer to evenly spray 0.5 kg of polydimethylsiloxane emulsion on the surface of the modified powder prepared in step S2 for 6 minutes, while maintaining the temperature in the reactor at 160° C.; after the spraying is completed, the temperature in the reactor is lowered to 140° C. and maintained at this temperature for 1 hour to promote complete evaporation of water in the material and ensure dehydration and drying of the powder to obtain a modifier.
[0087] Example 6
[0088] The preparation method of a polyurethane grouting material is basically the same as that of Example 1, the only difference being that the preparation method of the modifier is different.
[0089] The preparation method of the modifier is as follows:
[0090] S1, weighing 4kg bentonite, 1.6kg nano-silicon powder, 0.6kg sodium aluminate and 0.8kg kaolin as starting materials; mixing these materials in a blender at a rate of 2000 rpm for 20 minutes to ensure that the components are evenly dispersed to form a consistent mixed powder;
[0091] S2. The mixed powder obtained in step S1 is transferred to a reactor. During this process, 0.5 kg of a surfactant is added, wherein the surfactant is sodium palmitate and glycerol monostearate in a mass ratio of 3:2, and the system is heated to 160° C. and maintained at this temperature for 30 minutes for an adsorption modification process to form a modified powder;
[0092] S3. Use a sprayer to evenly spray 0.5 kg of polymethylphenylsiloxane on the surface of the modified powder prepared in step S2 for 6 minutes, while maintaining the temperature in the reactor at 160° C.; after the spraying is completed, the temperature in the reactor is lowered to 140° C. and maintained at this temperature for 1 hour to promote complete evaporation of water in the material and ensure dehydration and drying of the powder to obtain a modifier.
[0093] Example 7
[0094] The preparation method of a polyurethane grouting material is basically the same as that of Example 1, the only difference being that the preparation method of the modifier is different.
[0095] The preparation method of the modifier is as follows:
[0096] S1, weighing 4kg bentonite, 1.6kg nano-silicon powder, 0.6kg sodium aluminate and 0.8kg kaolin as starting materials; mixing these materials in a blender at a rate of 2000 rpm for 20 minutes to ensure that the components are evenly dispersed to form a consistent mixed powder;
[0097] S2. The mixed powder obtained in step S1 is transferred to a reactor. During this process, 0.5 kg of a surfactant is added, wherein the surfactant is sodium palmitate and glycerol monostearate in a mass ratio of 3:2, and the system is heated to 160° C. and maintained at this temperature for 30 minutes for an adsorption modification process to form a modified powder;
[0098] S3. Use a sprayer to evenly spray 0.5 kg of polymethylhydrogensiloxane on the surface of the modified powder prepared in step S2 for 6 minutes, while maintaining the temperature in the reactor at 160° C.; after the spraying is completed, the temperature in the reactor is lowered to 140° C. and maintained at this temperature for 1 hour to promote complete evaporation of water in the material and ensure dehydration and drying of the powder to obtain a modifier.
[0099] Comparative Example 1
[0100] The preparation method of a polyurethane grouting material is basically the same as that of Example 1, the only difference being the functional agent.
[0101] The functional agent is a mixture of polyamide wax and terpene resin in a weight ratio of 3:3.
[0102] Comparative Example 2
[0103] A preparation method of polyurethane grouting material is as follows:
[0104] Step 1, add 20kg of polyether polyol 400 and 15kg of diisononyl phthalate into a reaction vessel equipped with vacuum distillation and stirring functions, heat to 105°C, and dehydrate for 1 hour under a vacuum environment of 0.085MPa. After dehydration, lower the reaction temperature to 70°C, add 9kg of hexamethylene diisocyanate under normal pressure, maintain the reaction temperature at 75°C, and continue the reaction for 4 hours to form a pretreated product;
[0105] Step 2, 15 kg of polyether diol 210 and 12 kg of dimethylsiloxane are mixed, and the mixture is heated to 110° C. in a reaction vessel with vacuum distillation and stirring; a dehydration treatment is performed for 1 hour under a vacuum condition of 0.085 MPa; after the dehydration is completed, the mixture is cooled to 70° C., and 12 kg of polymethylene polyphenyl polyisocyanate is added under normal pressure; the temperature is controlled at 75° C., and the treatment is continued for 4 hours to prepare a reinforcing agent;
[0106] Step 3: Cool the pretreated material obtained in step 1 to 60°C. At this temperature, add the reinforcing agent obtained in step 2 to the pretreated material, stir it in a vacuum environment of 0.085MPa and perform vacuum degassing for 20 minutes to ensure that the mixture is uniform and remove bubbles. Finally, add 4kg of xylene and stir it for 10 minutes to obtain a polyurethane grouting material.
[0107] Test Example 1
[0108] Shrinkage performance test
[0109] The purpose of this experiment is to determine the shrinkage properties of a material by measuring the volume change over a specified time period. Before the experiment begins, a certain amount of sample is accurately weighed and carried out under controlled environmental conditions.
[0110] Experimental steps:
[0111] Under standard ambient conditions, accurately weigh 50.0 ± 0.1 g of the sample and place it in a dry measuring cup with a 500 ml scale.
[0112] Pour 100 ml of water into the measuring cup containing the sample and stir rapidly for about 10 seconds until the foaming is observed to stop.
[0113] After the foaming is completed, continue to add water to the measuring cup until it reaches the 500 ml mark, and record the amount of water added at this time, recorded as V1 (ml).
[0114] The samples were removed from the mixture and placed under standard experimental conditions for 168 hours (7 days).
[0115] After 168 hours, put the sample back into another 500 ml dry measuring cup and add water to the 500 ml mark. Record the amount of water required at this time, which is recorded as V2 (ml).
[0116] The shrinkage ratio of the sample after 168 hours is calculated according to formula (1):
[0117] S=(V1-V2) / (500-V1)×100%
[0118] Where:
[0119] S: shrinkage ratio of the sample after 168 hours, expressed as a percentage (%);
[0120] V1: The volume of water added for the first time, in milliliters (mL);
[0121] V2: The volume of water added for the second time, in milliliters (mL).
[0122] Take three samples and measure them three times according to this method. The average of the three measurement results is the test result. The test results are shown in Table 1.
[0123] Table 1
[0124] Experimental protocol 168h Volume shrinkage (%) Example 1 0.039 Example 2 0.045 Example 3 0.047 Example 4 0.051 Example 5 0.052 Example 6 0.055 Example 7 0.056 Comparative Example 1 0.063 Comparative Example 2 0.082
[0125] Test Example 2
[0126] Wet-dry cycle expansion test
[0127] This test is used to determine the volume expansion performance of materials under dry-wet cycle conditions to simulate the water absorption and drying process that may be encountered in actual use environment.
[0128] Test steps:
[0129] In a controlled standard experimental environment, accurately weigh 20.0±0.1g of the sample and place it in a 500ml measuring cup. Add 100ml of water to the measuring cup and stir rapidly for about 10 seconds until the foaming reaction is observed to be complete, then add water to the 500ml mark and let it stand for 24 hours under standard conditions. Take the solid body out of the solution, remove the surface moisture, and measure its volume by the water displacement method, which is recorded as V3.
[0130] The measured solid body was placed in a forced air drying oven at 80 degrees Celsius for 48 hours, and then further dried in a desiccator under standard experimental conditions for 2 hours. The dried solid body was placed back in a beaker containing 500 ml of water and allowed to stand for another 24 hours. After that, it was taken out and the surface moisture was removed. The volume was measured again using the water displacement method and recorded as V4.
[0131] The repeated expansion effect of the sample is calculated according to the following formula:
[0132] T=(V4-V3) / V3×100%
[0133] Where: T——specimen repeated expansion effect (%);
[0134] V3——water expansion volume during reaction (mL);
[0135] V4——expansion volume after water absorption after water loss (mL).
[0136] The average of the three test results is taken as the test result.
[0137] The test results are shown in Table 2.
[0138] Table 2
[0139]
[0140]
[0141] It can be seen from the data in Table 1 and Table 2 that the polyurethane grouting material prepared in Example 1 has lower volume shrinkage and dry-wet cycle expansion.
[0142] Compared with Example 1, the reason why the volume shrinkage and dry-wet cycle expansion of Examples 2 to 4 are higher may be related to the type of surfactant. In these examples, although the combination ratio of surfactant and glycerol monostearate is the same, the main surfactants are sodium dodecyl sulfate, sodium laurate and sodium stearate, respectively, and the chemical structure and properties of these surfactants are different from those of sodium palmitate used in Example 1. Sodium palmitate is an anionic surfactant with good wettability and dispersibility, which can promote more uniform adsorption and dispersion in the preparation process of modified powder, while glycerol monostearate, as a non-ionic surfactant, provides good emulsification and stability. This combination may form a more stable and uniform dispersion system in the preparation process of modified powder, which helps to reduce the aggregation of powder and form a denser structure, thereby reducing porosity and improving the volume stability of the material. Although sodium dodecyl sulfate, sodium laurate and sodium stearate also have surface activity, their molecular structure and hydrophilic-lipophilic balance (HLB value) may be different from sodium palmitate, which may cause their adsorption and dispersion effects in the modification process to be inferior to sodium palmitate, thereby affecting the structure and performance of the final material. In addition, the choice of surfactant also affects the interfacial tension and foam stability of the material, which may also indirectly affect the volume shrinkage and expansion properties of the material. For example, if the surfactant causes a decrease in foam stability, more pores may be formed in the material, thereby increasing the volume shrinkage rate. On the contrary, if the surfactant helps to form a more stable foam structure, it may reduce the shrinkage of the material.
[0143] Example 1 uses a fluorocarbon emulsion, while Examples 5 to 7 use polydimethylsiloxane emulsion, polymethylphenylsiloxane, and polymethylhydrogensiloxane, respectively. Fluorocarbon emulsions, due to their unique chemical structure, provide excellent hydrophobicity and durability, which may help to form a more stable and uniform dispersion system in the grouting material, reduce the penetration of water, thereby reducing the volume shrinkage of the material and improving its stability in dry-wet cycles. For Examples 5 to 7, although different types of silicone emulsions are used, they may not be as good as fluorocarbon emulsions in terms of hydrophobicity and durability. The molecular structure and surface activity of these emulsions may affect their dispersibility and adsorption capacity in the modified powder, and then affect the pore structure and moisture retention capacity of the final material. For example, silicone emulsions may not be as compatible with modified powders as fluorocarbon emulsions during high temperature and long-term heating, resulting in more pores in the material during drying, which will increase the volume shrinkage of the material and show greater expansion in dry-wet cycles. In addition, the stability of the emulsion and its interaction with the powder material may also affect the final performance of the material. If the emulsion cannot be evenly dispersed or reacts adversely with other components during the modification process, it may lead to inhomogeneity in the material structure, thus affecting its stability and expansion properties in long-term dry-wet cycles.
[0144] Example 1 shows lower volume shrinkage and dry-wet cycle expansion than Comparative Examples 1 and 2, which is mainly due to the addition of its unique functional agent. The functional agent is composed of a variety of components, including polyamide wax, modifier and terpene resin, which are mixed in a specific weight ratio and can significantly improve the performance of polyurethane grouting material. Polyamide wax, as an additive, can improve the lubricity and dispersibility of the material, help reduce friction during material mixing, thereby reducing water evaporation caused by frictional heat and reducing material shrinkage. Terpene resin, due to its high viscosity and flexibility, helps to improve the bonding performance and flexibility of the grouting material, making the material more adaptable to slight changes in the structure and reducing volume changes caused by changes in the external environment. The most critical thing is the fluorocarbon emulsion in the modifier, which gives the grouting material excellent hydrophobic properties and durability. The fluorocarbon emulsion forms a protective film on the surface of the modified powder, which can not only resist the penetration of water, but also form a low surface energy interface on the surface of the material, further reducing the contact between water and the material, thereby effectively reducing the water absorption and shrinkage of the material.
Claims
1. A method for preparing a polyurethane grouting material, characterized in that: The urethane grouting material is composed of the following components in parts by weight: 15 to 25 parts of polyether polyol 400, 12 to 19 parts of functional agent, 8 to 10 parts of hexamethylene diisocyanate, 13 to 18 parts of polyether diol 210, 10 to 15 parts of dimethylsiloxane, 10 to 15 parts of polymethylene polyphenyl polyisocyanate, 13 to 18 parts of diisononyl phthalate, and 3 to 5 parts of xylene.
2. The method for preparing the polyurethane grouting material according to claim 1, characterized in that: Here’s how: Step 1, polyether polyol 400 and diisononyl phthalate are mixed with a functional agent, added into a reaction vessel equipped with vacuum reduced pressure distillation and stirring functions, the mixture is heated to 100-110° C., and dehydrated. After dehydration, the reaction temperature is lowered to 60-80° C., hexamethylene diisocyanate is added under normal pressure, the reaction temperature is maintained at 70-80° C., and the reaction is continued for 2-5 hours to form a pretreated product; Step 2, polyether diol 210, functional agent and dimethylsiloxane are mixed, and heated to 100-120° C. in a reaction vessel with vacuum distillation and stirring; dehydration treatment; after dehydration, the temperature is lowered to 60-80° C., and polymethylene polyphenyl polyisocyanate is added under normal pressure; the temperature is controlled at 70-80° C., and the treatment is continued for 2-5 hours to prepare a reinforcing agent; Step 3: Cool the pretreated material obtained in step 1 to 50-70° C. At this temperature, add the reinforcing agent obtained in step 2 to the pretreated material, degas the material to ensure that the mixture is uniform and remove bubbles, and finally, add xylene and stir for 5-15 minutes to obtain a polyurethane grouting material.
3. The method for preparing the polyurethane grouting material according to claim 1 or 2, characterized in that: The functional agent is a mixture of a thixotropic agent, a modifier and a terpene resin in a weight ratio of 2-4:3-5:2-4.
4. The method for preparing the polyurethane grouting material according to claim 3, characterized in that: The thixotropic agent is one or more of polyamide wax, polyethylene wax, castor oil, bentonite, fumed silica, kaolin, calcium carbonate and attapulgite.
5. The method for preparing the polyurethane grouting material according to claim 2, characterized in that: The dehydration treatment in step 1 and step 2 is independently performed under a vacuum environment of 0.08 to 0.09 MPa for 0.5 to 2 hours.
6. The method for preparing the polyurethane grouting material according to claim 2, characterized in that: The degassing treatment in step 3 is to stir in a vacuum environment of 0.08 to 0.09 MPa and perform vacuum degassing treatment for 10 to 30 minutes.
7. The method for preparing the polyurethane grouting material according to claim 3, characterized in that: The preparation method of the modifier is as follows, in parts by weight: S1, weighing 3-5 parts of bentonite, 1-2 parts of nano-silicon powder, 0.4-0.8 parts of sodium aluminate and 0.5-1 parts of kaolin as starting materials; mixing these raw materials in a blender at a speed of 1500-2500 rpm for 10-30 minutes to form a consistent mixed powder; S2, transferring the mixed powder obtained in step S1 to a reaction kettle, during which 0.4 to 0.6 parts of a surfactant are added, and the system is heated to 150 to 170° C. and maintained at this temperature for 20 to 40 minutes to form a modified powder; S3. Use a sprayer to evenly spray 0.4 to 0.6 parts of fluorocarbon emulsion on the surface of the modified powder prepared in step S2 for 3 to 10 minutes, while maintaining the temperature in the reactor at 160°C; after the spraying is completed, reduce the temperature in the reactor to 130 to 150°C and maintain it at this temperature for 0.5 to 2 hours to obtain a modifier.
8. The method for preparing the polyurethane grouting material according to claim 7, characterized in that: The surfactant is composed of sodium palmitate and glycerol monostearate in a mass ratio of 2-4:1-3.
9. A polyurethane grouting material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A low-foaming, high-adhesion, elastic polyurethane grout and its preparation method
CN112876635B